(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Dietary phytochemicals are considered as an effective tool to cure various human physiological disorders. The leaves of Moringa oleifera are rich in bioactive compounds, and reported to possess various pharmacological activities. Therefore, we aimed for quantitative estimation of phytochemicals present in M. oleifera leaves and determination antioxidant activities of leaf parts of M. oleifera. Leaves of M. oleifera was subjected to successive solvent extraction by continuous hot extraction (Soxhlet) with 50% methanol. The free radical scavenging activity of the methanolic leaf extract of M. oleifera and of standard ascorbic acid were investigated using 1,1-diphenyl-2-picrylhydrazyl (DPPH) radical scavenging method. Results portrayed that methanolic leaf extract of M. oleifera exhibited inhibition percentage of 4.56%, 7.89%, 15.82%, and 31.58% at a concentration range of 25µg/mL, 50µg/mL, 100µg/mL, and 200µg/mL respectively with an IC50 value of 38.48 µg/mL in comparison with the standard ascorbic acid with an IC50 value of 53.54 µg/mL. In conclusion, the presence of secondary metabolites especially polyphenols in the methanolic leaf extract of M. oleifera led to the demonstration of its antioxidant properties. Therefore, methanolic leaf extract of M. oleifera could be exploited in the development of polyherbal formulations with antioxidant claims.